Usability prioritization using performance metrics and hierarchical agglomerative clustering in MAR-learning application - Cheng L.K.; Selamat A.; Mohamed Zabil M.H.; Selamat M.H.; Alias R.A.; Puteh F.; Mohamed F.; Krejcar O. (IOS Press, 2023)
Artificial intelligence; Augmented reality; Cluster analysis; Computer aided instruction; Learning systems; Usability engineering; Agglomerative clustering; English language teaching; Mobile augmented reality; Unsupervised machine learning; Usability; Learning algorithms